2010
DOI: 10.4049/jimmunol.0903675
|View full text |Cite
|
Sign up to set email alerts
|

Amphioxus SARM Involved in Neural Development May Function as a Suppressor of TLR Signaling

Abstract: Among five Toll/IL-1R resistance adaptors, sterile α and Toll/IL-1R resistance motif containing protein (SARM) is the only one conserved from Caenorhabditis elegans to human. However, its physiologic roles are hardly understood, and its involvement in TLR signaling remains debatable. In this study, we first demonstrated a predominant expression of amphioxus SARM (Branchiostoma belcheri tsingtauense SARM) in neural cells during embryogenesis and its predominant expression in the digestive system from larva to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…Con- versely, TRAF1, TRAF4 and SARM act as inhibitors in TICAM1-dependent signaling [33][34][35][36]. As amphioxus TRAF2, TRAF3, TRAF4, TRAF6, and SARM were cloned by our group in other studies [37][38][39], we investigated the relationship between these molecules and bbt-TICAM. The results showed that bbtTRAF3, bbtTRAF4, and bbtTRAF6 had no effect on the NF-κB activation mediated by bbtTICAM (Supplementary information, Figure S5A-S5C), while bbtTRAF2 and bbtSARM attenuated the activity of bbtTICAM in a dose-dependent manner ( Figure 7A and 7B).…”
Section: Bbtticam Failed To Interact With Bbttraf3 4 and 6 But Assmentioning
confidence: 99%
“…Con- versely, TRAF1, TRAF4 and SARM act as inhibitors in TICAM1-dependent signaling [33][34][35][36]. As amphioxus TRAF2, TRAF3, TRAF4, TRAF6, and SARM were cloned by our group in other studies [37][38][39], we investigated the relationship between these molecules and bbt-TICAM. The results showed that bbtTRAF3, bbtTRAF4, and bbtTRAF6 had no effect on the NF-κB activation mediated by bbtTICAM (Supplementary information, Figure S5A-S5C), while bbtTRAF2 and bbtSARM attenuated the activity of bbtTICAM in a dose-dependent manner ( Figure 7A and 7B).…”
Section: Bbtticam Failed To Interact With Bbttraf3 4 and 6 But Assmentioning
confidence: 99%
“…In our previous studies of amphioxus TLRs and related signaling molecules, we provided compelling evidence for a functional intracellular TLR-NF-kB signaling cascade (25,31,32,34). Amphioxus expresses $48 TLRs and .40 TIR-containing adaptors, which suggests an expanded repertoire of adaptors and intermediate signal transducers in its TLR signaling pathways.…”
Section: Oomentioning
confidence: 99%
“…Embryo collection, section in situ hybridization, Southern blot hybridization, RT-PCR analysis, immunofluorescence imaging, transient transfection, luciferase reporter assay, and coimmunoprecipitation (co-IP) were performed as described previously (23)(24)(25). Primers for hybridization probe preparation and RT-PCR are listed in Supplemental Table I.…”
Section: Nuclear Extraction and Emsamentioning
confidence: 99%
“…To reduce microbial abundance, on the day prior to dissection, amphioxi were transferred to sea water that was filtered with a 0.45-mm filter and contained 10 mg/ml penicillin. After amphioxi were anesthetized, the amphioxus intestines were extracted, dissected into pieces, and digested for 2 h at 23˚C with 1% collagenase type II (Life Sectional in situ hybridization was performed according to the protocol described previously (34). Luciferase reporter assay, Co-IP, FIGURE 1.…”
Section: Culture Of Amphioxus Intestinal Cells and Poly(i:c) Transfecmentioning
confidence: 99%